Analfabetismo e alfabetização: representações de professoras-alfabetizadoras de camponeses quilombolas jovens e adultos - Sá, Maria Reneude de (2012)
Settling in Brazil since colonial times, illiteracy is becoming, increasingly, a historical problem. In addition to the denial of a constitutional right granted to all citizens, the illiterate condition reduces the exercise of citizenship in the contemporary world. Its existence uneasy social and human sciences researcher who seek carry studies that can contribute to their understanding and facing. In this work I decided to develop a study on illiteracy through the analysis of representations about this issue from literacy-teachers of young and adult peasants descendent of historical African people (quilombolas), relating these representations to their socio-economic and cultural context and to their teacher training. For this, I adopted a qualitative methodology with ethnographic research conducted in the year 2010 in Muquém community, descendent of the Quilombo dos Palmares, located in the municipality of União dos Palmares, in Alagoas state. The results of the analysis showed, in the construction of representations of the teachers on alphabetization and illiteracy, fragments of formal knowledge, acquired, probably in teacher training activities, reading material of the specific area, such as the textbook used in alphabetization classes, among others; established beliefs in the collective imaginary about illiteracy and literacy; and on knowledge developed in and about their own teaching practice in the exercise of literacy; exchange experiences with their peers in several situations, among other sources of knowledge. Through their representations, the teachers seek explanations and justifications that respond to their concerns in the classroom. Sometimes these representations indicate the concealment of issues related to the teaching practice, which may be contributing to the problem of illiteracy, sometimes advertise possibilities for change. Among the conclusive considerations, the study shows the importance of priority in the formation courses for teacher, a fundamental principle advocated by Paulo Freire, from his early studies in the 1950s - a critical reflection on practice, allowing for the teachers to revise their views and redirect their pedagogical practices